2007
DOI: 10.1523/jneurosci.3667-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Associated Stimuli Increase Cocaine Seeking and Activate Accumbens Core Neurons after Abstinence

Abstract: Electrophysiological recordings were completed in rats (n ϭ 14) trained to self-administer cocaine to determine whether activation of nucleus accumbens (Acb) neurons (core vs shell) by cocaine-associated stimuli is enhanced after 1 month of cocaine abstinence. After self-administration training, 170 cells were recorded during a single test session conducted either the next day or 1 month later. The test session consisted of three phases during which (1) the cocaine cue was presented unexpectedly to rats, (2) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
112
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 31 publications
28
112
1
2
Order By: Relevance
“…In a subsequent study, we also showed that NAc core neurons are more responsive to cocaineassociated cues following 1-month abstinence (Hollander and Carelli, 2007). In this study, animals were trained to self-administer cocaine then returned to their home cages without cocaine access for either 1 day or 1 month.…”
Section: Cocaine Abstinence Alters Nac Cell Firingmentioning
confidence: 70%
“…In a subsequent study, we also showed that NAc core neurons are more responsive to cocaineassociated cues following 1-month abstinence (Hollander and Carelli, 2007). In this study, animals were trained to self-administer cocaine then returned to their home cages without cocaine access for either 1 day or 1 month.…”
Section: Cocaine Abstinence Alters Nac Cell Firingmentioning
confidence: 70%
“…Accordingly, we have shown that, in RHA rats sensitized to cocaine, the increment in dopamine efflux elicited by the administration of a cocaine challenge after 1 week of abstinence is potentiated in the NAc-core and concomitantly attenuated in the NAc-shell, whereas such adaptive changes are not observed in sensitization-resistant RLA rats (Giorgi et al, 2007). Importantly, the NAc-core has been implicated in the reinstatement of cocaine-seeking induced by the administration of a priming dose of the drug or by exposure to drug-related cues (Ito et al, 2004;Hollander and Carelli, 2007). These findings support the view that the NAc-core and its afferent glutamatergic projections originating in the mPFC play a key role in cocaine-induced relapse (McFarland et al, 2003).…”
Section: Figurementioning
confidence: 99%
“…It has been proposed that these neural circuits encode and associate information about a primary reinforcer like cocaine with motivated behavior and/or environmental stimuli (Everitt and Wolf, 2002;Schultz, 2002;Hollander and Carelli, 2007). Adaptive changes in this neural circuitry are also believed to underlie the long-term increment in the locomotor activation of rodents (ie, behavioral sensitization) elicited by the repeated exposure to cocaine (Vanderschuren and Kalivas, 2000;Nestler, 2001;Li et al, 2004;Vezina, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting their critical roles in the neural circuitry of drug-seeking behavior, these regions have also been identified using preclinical reinstatement models (8,9). For example, NAc neurons exhibit conditioned responses to drugassociated environmental stimuli even after prolonged drug abstinence, suggesting persistent alterations in reward-related information processing (10), whereas inactivation of the dorsal prefrontal cortex (PFC) or basolateral amygdala blocks cue-induced reinstatement (11).…”
mentioning
confidence: 99%